Comparative analysis of aging processes in animal fat and dry aging in a beef chest cut - Valencia-Fajardo, Rafael (2024)
Beef aging is a process that involves the interaction of enzymes and chemical transformations that directly influence changes in flavor and texture, which in turn can determine the sensory experience for guests. The purpose of this study was to compare, in terms of texture, the aging of beef brisket cuts through two techniques: with animal fat coating and dry aging, over a period of 21 days, and to determine the acceptability of end consumers. The cuts were stored under controlled temperature and moisture conditions (2 °C and 60 % relative moisture, respectively), with continuous monitoring to ensure food safety. Finally, they were cut into 2 cm thick steaks, fried to medium doneness with salt, and sensorially evaluated by a panel of 27 individuals. The results revealed an acceptance rate of 74.1 % for the meat sample aged with animal fat, surpassing the dry-aged sample (22.3 %) and the control (non-aged sample). It was concluded that aging with animal fat was the most suitable, due to the achieved tenderness and flavor. This is attributed to the promotion of protease activity as the main agents in proteolysis and denaturation due to pH effects on myofibrillar proteins. Additionally, it was highlighted that aging is possible for this beef cut, which is not commonly used in such situations due to its low intramuscular fat content."